Adsorption of Methylene Blue Dyes Using Pectin Membrane. (July 2020) - Hastuti, Budi; Nur Afifah, Siti; Mulyani, Bakti; Susilowati, Endang
Abstract: Environmental pollution caused by methylene blue textile dyes is very dangerous for the aquatic environment and human health. To overcome this problem, various adsorbents have been developed for the processing of methylene blue liquid waste. This aim of this research is to know the ability of pectin membrane toward methylene blue dyes. Pectin is a biomaterial isolated from the plant cell walls. Pectin is an anionic polymer, many contain active groups which able to bind positive ions of methylene blue. This method of this research is an experimental method in the laboratory. Pectin adsorbent membrane was made by dissolving of pectin into a 5% acetic acid solution. The optimal condition of the adsorption of methylene blue by pectin membrane was determine. The functional groups of pectin membranes were analyzed by infra red spectroscopy. The adsorption of methylene blue was analysis by using Ultraviolet-Visible Spectroscopy. The characterization of FTIR showed that pectin membranes have carboxyl and hydroxyl active groups. The results showed that the optimum condition of the adsorption process of methylene blue dye was within pH 4 with adsorption capacity of 0.75 mg/g and 60 minutes of contact time with adsorption capacity 17.64 mg/g. The optimum adsorption capacity of pectin membranes in adsorbing methylene blue was 19.39 mg /g